Tradition and historical reconstruction in modern Church art on the example of the “Apocalypse” by Nikolai Masteropulo (from the point of view of the Medievalist) - Yu. N. Buzykina (Российский журнал истории Церкви)
The article deals with Apocalypse cycle of cloisonné enamels created in the early 2000-s by Russian and Greek artist Nilolaos Masteropoulos. The article analyses the concept of this creation, conceived as an actual art work made by medieval tool — ancient technique of cloisonné enamel, reconstructed and reconceived by the artist. The choice of the old technique which disappeared in byzantine tradition in 13th century is united with the subject which was not typical for byzantine art at all and appeared only in the early 15th century in the wall painting of Annunciation Cathedral of Moscow Kremlin, ordered by Russian prince and painted by Byzantine artist Theophanes the Greek. This union, demonstrating the artist’s deep knowledge in the art history and scientific literature, does not turn this Apocalypse into intellectual rebus or kind of historical reconstruction. Reviving ancient techniques and using ancient symbols, Nikolaos Masteropulos created an actual art work, intended for beholding by his contemporaries.